2010
DOI: 10.1586/erd.10.46
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography for the diagnosis of liver fibrosis

Abstract: Transient elastography (FibroScan(®)) is a noninvasive method proposed for the assessment of liver fibrosis in patients with chronic liver diseases by measuring liver stiffness. It can be easily performed at the bedside or in the outpatient clinic with immediate results and good reproducibility. FibroScan is validated for the diagnosis of significant fibrosis and cirrhosis in chronic hepatitis C, in recurrence of hepatitis C after liver transplantation, in co-infected HIV-HCV patients, in chronic hepatitis B, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 77 publications
(35 reference statements)
3
62
0
4
Order By: Relevance
“…Indeed, we know that each disease has specific cut-offs for each stage of fibrosis. Large prospective studies with XL probe are needed to propose specific cut-off values for each stage of fibrosis, for each disease [6,8] the aim of our study was not to propose cut-offs for each stage of fibrosis but to compare the feasibility of the M and XL probes. Secondly, liver biopsy was used as the gold standard, and liver biopsies were assessed by two pathologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we know that each disease has specific cut-offs for each stage of fibrosis. Large prospective studies with XL probe are needed to propose specific cut-off values for each stage of fibrosis, for each disease [6,8] the aim of our study was not to propose cut-offs for each stage of fibrosis but to compare the feasibility of the M and XL probes. Secondly, liver biopsy was used as the gold standard, and liver biopsies were assessed by two pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…It has a high degree of accuracy and reproducibility in predicting bridging fibrosis and cirrhosis in patients with chronic liver diseases, especially NAFLD [6][7][8][9][10]. In a recent study, we found that in 246 NAFLD patients the area under the receiver-operating characteristics curve (AUROC) of liver stiffness measurement for F3 or higher and F4 disease was 0.93 and 0.95, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several serological fibrosis scores have been evaluated in viral liver disease with adequate diagnostic performance [11]. However, accuracy and cutoff values of ultrasoundbased methods and fibrosis biomarkers depend on the etiology of the underlying disease and should be calculated separately for each entity [12,13]. Fibroscan Ò , ARFI, and laboratory-based indices have only been rarely investigated in WD so far, because patients suffer from an orphan disease, and representative patient cohorts exist only in specialized referral centers.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity measurements are computer-processed and the final result is the average of 10 measurements. Known limitations of this method are: a significant degree of obesity, pregnancy, and the presence of ascites [12].…”
Section: Elastography Fibroscanmentioning
confidence: 99%